2011
DOI: 10.1080/13676261.2011.580523
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian youth looking towards the future

Abstract: Selected survey data on future aspirations and expectations from 3565 young Indonesians are presented in this study. Muslim-majority Indonesia is an Asian economic success story. The economy has seen solid growth, leading to an expansion of the private sector. The upward credentialling of the labour market and the rapid growth of the middle class have resulted. Accordingly, the transition to adulthood for working-class and lower middle-class youth has been extended by the necessity to complete schooling and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
1
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 26 publications
1
38
1
14
Order By: Relevance
“…Remaja awal di Indonesia masih tergantung pada keluarga dan diperlakukan sebagai individu yang belum dewasa sehingga mereka akan mematuhi keinginan atau harapan orang tua dan mengabaikan keinginan pribadinya (Nilan, Parker, Bennett, & Robinson, 2011). Selain itu, berbagai domain identitas (misalnya karier) belum menjadi masalah konkret bagi remaja awal di Indonesia yang pada umumnya masih menempuh pendidikan di Sekolah Menengah Pertama (Sarwono, 2013).…”
Section: Diskusiunclassified
“…Remaja awal di Indonesia masih tergantung pada keluarga dan diperlakukan sebagai individu yang belum dewasa sehingga mereka akan mematuhi keinginan atau harapan orang tua dan mengabaikan keinginan pribadinya (Nilan, Parker, Bennett, & Robinson, 2011). Selain itu, berbagai domain identitas (misalnya karier) belum menjadi masalah konkret bagi remaja awal di Indonesia yang pada umumnya masih menempuh pendidikan di Sekolah Menengah Pertama (Sarwono, 2013).…”
Section: Diskusiunclassified
“…Much of the published literature on Indonesian youth to date has been focused on young people who are still participating in education (Parker 1997(Parker , 2009Nilan et al 2011), who are still living under the care of their natal families or other relatives (Bennett 2005), and who have the economic means to participate in highly commodified and increasingly globalized youth cultures (Beazley 2008;Luvaas 2009Luvaas , 2010Nilan 2008). The young people who have typically been the subjects of social research in Indonesia have tended to be middle class, unmarried, viewed as still dependent upon their natal families and pre-adult in their social status.…”
Section: Introductionmentioning
confidence: 99%
“…Our study confirmed that religion is an important part of everyday life in Indonesia. And three religious groups out of six in all, which are Muslim, Christian and Hindu Indonesians, take their religious practice seriously (Adney-Risakotta, 2009;Nilan, Parker, Bennett, Robinson, 2011). The Muslim parents' beliefs in the importance of religion were well translated in their parenting styles with gentle approaches to their children without any use of physical punishment.…”
Section: Discussionmentioning
confidence: 99%
“…Best example that challenges our misperception about Muslim is Indonesia. The largest Muslim majority country in the world is Indonesia, not a country in the Middle East (Nilan, Parker, Bennett, & Robinson, 2011). It is necessary to provide some background information about Indonesia and its Muslim population.…”
mentioning
confidence: 99%